Human and mouse Mx proteins inhibit different steps of the influenza virus multiplication cycle. - Pavlovic, J (1992)
Human MxA and mouse Mx1 are interferon-induced proteins capable of inhibiting the multiplication of influenza virus. MxA protein is localized in the cytoplasm, whereas Mx1 protein accumulates in the nucleus. Taking advantage of stably transfected cell lines that constitutively express either MxA or Mx1 protein, we examined the steps at which these proteins block influenza A viruses. In infected cells expressing MxA protein, all viral mRNAs synthesized as a result of primary transcription in the nucleus by the virion-associated RNA polymerase accumulated to normal levels. These primary viral transcripts were polyadenylated, were active in directing viral protein synthesis in vitro, and appeared to be efficiently transported to the cell cytoplasm. Yet viral protein synthesis and genome amplification were strongly inhibited, suggesting that MxA protein interfered with either intracytoplasmic transport of viral mRNAs, viral protein synthesis, or translocation of newly synthesized viral proteins to the cell nucleus. However, in infected cells expressing Mx1 protein, the concentrations of the longest primary transcripts encoding the three influenza virus polymerase proteins PB1, PB2, and PA were at least 50-fold reduced. Accumulation of the shorter primary transcripts encoding the other viral proteins was also inhibited but to a lesser extent. These results demonstrate that the mouse Mx1 protein interferes with primary transcription of influenza virus in the nucleus, whereas the human MxA protein inhibits a subsequent step that presumably takes place in the cytoplasm of infected cells.